Surface amorphisation of TiZrN coatings by laser carburisation. (3rd October 2018) - Kim, Taewoo; Hong, Eunpyo; Choi, Youngkue; Kim, Myunghyun; Lee, Heesoo
ABSTRACT: The enhancement of wear resistance by laser carburisation on TiZrN coatings was investigated in terms of bond state. Graphite paste was used to cover the TiZrN coatings and then pulsed laser ablation was used to solidify the carbon. Tribometer test showed that the friction coefficient was reduced from 0.64 to 0.17 after laser carburisation. The doped carbon was analysed as a mixture with sp 2 C and sp 3 C bonds using an X-ray photoelectron spectroscopy depth profile. The sp 2 /sp 3 ratio was 2.29 at the surface and increased up to 2.91 in the depth direction. To verify the effect of the hybrid bonds on the atomic order, annealing was carried out to the carburised specimens. As the ratio increased to 3.28, graphitisation resulting in transition from sp 3 to sp 2 was confirmed, and variation in the lattice structure was demonstrated by a reduction in the lattice constant (4.45 Å to 4.40 Å) using Rietveld refinement.